2019
DOI: 10.1002/lary.28074
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ossiculoplasty: Is there any edge over the microscopic technique?

Abstract: Objectives/Hypothesis To compare endoscopic ossiculoplasty with conventional microscopic technique in terms of postoperative hearing outcomes and complications. Study Design Randomized controlled trial. Methods One hundred eighteen patients diagnosed with ossicular chain discontinuity were randomly assigned into two groups, one undergoing endoscopic ossiculoplasty and the other undergoing ossiculoplasty by the microscopic technique, with the operating surgeon being same for both groups. The two groups were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…To our knowledge, our study is the largest to primarily investigate the results of endoscope-assisted total ossiculoplasty. In addition, our follow-up is longer than previously described in literature (1–3). Das et al (1) described significantly better hearing results 1 month after endoscope-assisted ossiculoplasty in comparison to microscope-assisted ossiculoplasty.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…To our knowledge, our study is the largest to primarily investigate the results of endoscope-assisted total ossiculoplasty. In addition, our follow-up is longer than previously described in literature (1–3). Das et al (1) described significantly better hearing results 1 month after endoscope-assisted ossiculoplasty in comparison to microscope-assisted ossiculoplasty.…”
Section: Discussionmentioning
confidence: 81%
“…Despite the frequent use of endoscopes in ear surgery, only three studies with a small number of endoscopically treated patients (n < 21) with a follow-up of less than 6 months have evaluated the endoscope's role in total ossiculoplasty. Das et al ( 1 ) described significantly better hearing results 1 month after endoscope-assisted ossiculoplasty in comparison to microscope-assisted ossiculoplasty. At 6 months after surgery both methods were shown to have comparable audiologic outcomes (endoscopic group: n = 14, follow-up 6 months, postoperative air bone gap (ABG) PTA 0.5-3kHz 26.2 dB).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (41)(42)(43)(44)(45)(46) have found TEES ossiculoplasty to be at least equivalent to the microscopic approach. We hypothesized that TEES ossiculoplasty would result in a similar audiometric outcomes compared with microscopic ossiculoplasty based on the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown equivalent or improved results from endoscopic versus microscope-guided tympanic membrane perforation closure and clearance of cholesteatoma in children (8,9). Research suggests that audiometric outcomes are equivalent in experienced hands between TEES and PAM approaches for most common procedures including tympanoplasty, ossiculoplasty, and stapedotomy (3,7,8,(10)(11)(12)(13). Because TEES allows surgeons to complete these procedures with less soft tissue dissection than by a post-auricular approach, examination of secondary patient outcomes related to surgical morbidity may demonstrate a potential benefit of TEES over post-auricular surgery.…”
Section: Objectivementioning
confidence: 99%